Review of the species of Strophedra Herrich-Schäffer, 1853 from China (Lepidoptera: Tortricidae: Olethreutinae: Grapholitini) - Lu, Sihan; Li, Houhun (Zootaxa, 2017)
The seven species of the genus Strophedra Herrich-Schäffer, 1853 recorded from China are reviewed. Four species, S. paraspinifera, sp. nov., S. nigrifusca, sp. nov., S. laticolla, sp. nov., and S. tricornuta, sp. nov., are described as new; S. quercivora (Meyrick, 1920) is newly recorded from China. Photos of adults and genitalia are provided, and a key to the Chinese species is included.